Arte Povera - Celant, Germano (Milano : Electa editrice, 1985)
Anselmo, Giovanni ; Boetti, Alighiero ; Calzolari, Pier Paolo ; Fabro, Luciano ; Kounellis, Jannis ; Merz, Mario ; Merz, Marisa ; Paolini, Giulio ; Pascali, Pino ; Penone, Giuseppe ; Pistoletto, Michelangelo ; Prini, Emilio ; Zorio, Gilberto
Italiaans & Engels
boek